2020
DOI: 10.13057/biodiv/d210303
|View full text |Cite
|
Sign up to set email alerts
|

Ex-situ population of White-rumped Shama (Copsychus malabaricus): studies of density, distribution and bird keepers in Bengkulu, Sumatra

Abstract: Abstract. Putranto HD, Brata B, Yumiati Y. 2020. Ex-situ population of White-rumped Shama (Copsychus malabaricus): Studies of density, distribution and bird keepers in Bengkulu, Sumatra. Biodiversitas 21: 865-874. Purpose of this research was to estimate number of White-rumped Shama (Copsychus malabaricus) or locally known as murai batu which are kept by Bengkulu's bird keepers, analyze its population density, population distribution, and the profile of bird keepers. Researcher used field observation method by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…Kelebihan burung murai batu membuat banyak penghobi kicauan berbondong-bondong mencari dan merawat calon-calon murai batu yang akan diperlombakan berapapun harganya tidak menjadi persoalan (Putranto et al, 2018). Tidak jarang pencarian hingga kepelosokpelosok dilakukan dan terkadang terjadi perburuan ke hutan yang membuat populasi burung murai batu berkurang (Putranto et al, 2019a, b) . Burung murai batu anakan yang berumur 2-3 bulan dapat dihargai Rp.2.000.000 -5.000.000 tergantung dengan kualitas indukannya dan dapat berharga hingga ratusan juta rupiah apabila sudah berprestasi dan banyak memenangkan lomba (Saputro et al, 2016).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Kelebihan burung murai batu membuat banyak penghobi kicauan berbondong-bondong mencari dan merawat calon-calon murai batu yang akan diperlombakan berapapun harganya tidak menjadi persoalan (Putranto et al, 2018). Tidak jarang pencarian hingga kepelosokpelosok dilakukan dan terkadang terjadi perburuan ke hutan yang membuat populasi burung murai batu berkurang (Putranto et al, 2019a, b) . Burung murai batu anakan yang berumur 2-3 bulan dapat dihargai Rp.2.000.000 -5.000.000 tergantung dengan kualitas indukannya dan dapat berharga hingga ratusan juta rupiah apabila sudah berprestasi dan banyak memenangkan lomba (Saputro et al, 2016).…”
Section: Pendahuluanunclassified
“…Lokasi penelitian ditentukan secara sengaja (purposive sampling) di Kota Bengkulu dengan pertimbangan bahwa Kota Bengkulu merupakan ibukota provinsi yang menjadi pusat perekonomian terbesar di Provinsi Bengkulu dan berdasarkan hasil penelitian Putranto et al (2019a) bahwa terdapat 68 orang pemelihara burung murai batu di Kota Bengkulu dan melakukan usaha penangkaran burung murai batu tersebar di beberapa kecamatan yang ada di Kota Bengkulu.…”
Section: Materi Dan Metode Metode Penentuan Lokasi Penelitianunclassified
“…The previous report stated that the habit of keeping birds has long been known in Indonesian society, and even in some cultures, this habit is still preserved traditionally (Iskandar et al 2016). Studies by Putranto et al (2019aPutranto et al ( , 2021 said hobbies, economic values, conservation, scientific studies, and even prestige or a high ranking level in a certain social status became the main reasons for bird keepers to have these birds as pets. In addition, a previous study reported that birds are kept giving satisfaction to their owners because they can provide a natural atmosphere in the form of beautiful appearances, colors, and songs (Putranto et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Keeping a favorite pet, such as White-rumped Shama or Copsychus malabaricus, can lead to an uncontrol situation, a decreasing population for some avian species in the wild caused by poaching (Putranto et al 2019a(Putranto et al , 2020(Putranto et al , 2021. However, scientific information about Indonesia's Whiterumped Shama birds, in terms of biological data and its intensive daily management in captivity and the wild, is still very limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation